A High‐Resolution Belemnite Geochemical Analysis of Early Cretaceous (Valanginian‐Hauterivian) Environmental and Climatic Perturbations. (18th October 2018) - Price, Gregory D.; Janssen, Nico M. M.; Martinez, Mathieu; Company, Miguel; Vandevelde, Justin H.; Grimes, Stephen T.
Abstract: The Early Cretaceous Weissert event, characterized by a positive carbon isotope excursion and coincident with the Paraná‐Etendeka volcanism, saw a biogeochemical chain of events that ultimately led to an increase in carbon burial. A conclusive link between the Paraná‐Etendeka volcanism and its impact upon the environment remains, however, elusive. Here we reconstruct temperature through the Weissert event from Mg/Ca ratios of belemnites from the Vocontian Trough (France) and SE Spain and use carbon isotopes to link our temperature reconstruction to marine records of carbon cycling. We provide evidence that the Paraná‐Etendeka volcanism, unlike some large igneous provinces, did not cause a climate warming. The case can be made for cooling in the last stages of the Weissert event, which possibly reflects substantial CO2 drawdown. In the absence of warming and consequent accelerated hydrological cycling and the relatively long duration of the eruptive phase of the Paraná‐Etendeka, an alternate trigger for increased fertilization of the oceans is implicated. Key Points: A high‐resolution carbon and oxygen isotope record for the Early Cretaceous A robust characterization of Valanginian temperature evolution Carbonate oxygen isotope signal is primarily driven by seawater oxygen isotope changes and not temperature